2017
DOI: 10.1093/ofid/ofx247
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Arbovirus Outbreaks: When Chikungunya Virus Hits More Precarious Populations Than Dengue Virus in French Guiana

Abstract: BackgroundSince 2013, 3 successive arbovirus outbreaks, dengue (DENV), chikungunya (CHIKV), and Zika virus, have occurred in French Guiana (FG). The primary objective of this study was to describe the socioeconomic indicators of the first patients infected with CHIKV during the outbreak of 2014. The secondary objective was to compare those patients with patient infected by DENV and with the local population.MethodsA monocentric, retrospective, case-control study was conducted in Cayenne hospital in FG comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
4
35
0
2
Order By: Relevance
“…In Rio de Janeiro city, areas in or near favelas were detected as hot spots for dengue [39]. Consistent with our findings, a study conducted in French Guiana indicated that, early in the epidemic, the poorest neighbourhoods would have a greater risk for CHIKV infection [41]. In the first dengue epidemic in a city of São Paulo state, Brazil, authors found a direct relationship between low socio-economic conditions and dengue [42].…”
Section: Dengue Chikungunya and Zika Multivariate Clusterssupporting
confidence: 89%
“…In Rio de Janeiro city, areas in or near favelas were detected as hot spots for dengue [39]. Consistent with our findings, a study conducted in French Guiana indicated that, early in the epidemic, the poorest neighbourhoods would have a greater risk for CHIKV infection [41]. In the first dengue epidemic in a city of São Paulo state, Brazil, authors found a direct relationship between low socio-economic conditions and dengue [42].…”
Section: Dengue Chikungunya and Zika Multivariate Clusterssupporting
confidence: 89%
“…These results, previous observations on dengue and CHIKV, observations in patient with chronic diseases, in pregnant women, and in persons renouncing to health care all suggest that social inequalities of health often affect the same populations with poorer living conditions and reduced access to care and prevention. [4,12] The present results emphasize that population approaches for a range of selected problems may be more pertinent than an array of PLOS NEGLECTED TROPICAL DISEASES vertical social programs in different populations. Indeed, many community approaches are presently funded as thematic (HIV prevention and testing, addictions.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 69%
“…greater vector densities and transmission in these areas, whereas in rich neighborhoods populations were more likely to come from France and not be immunized thus being at risk for clinical disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical framework was confirmed in Mayotte where social disparities in infection rate were primarily structured by housing conditions as well as cognitive representations of the disease, ‘legitimate images’ being found in rich urban settings, ‘folk theories’ being found in poor suburban settings [ 15 ]. Interestingly, the neighbourhood environment was found different between dengue (or Zika) and CHIKF-affected populations in French Guiana and Rio Janeiro, Brazil, where CHIKF tended to impact the most impoverished communities living in overcrowded areas, which may explain the higher basic reproductive number (R0) for CHIKV than for flaviviruses [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%